Culture and the politics of Third World nationalism - Dawa Norbu, 1949- (London ; New York : Routledge, 1992)
Nationalism in specific political systems combined with a theoretical framework that draws out its universal significance. Ten case studies from South Asia, the Middle East, Latin America and Europe focus on local cultural factors.
Book Cover; Title; Contents; List of figures; List of tables; Preface: field experience and social theory; Introduction: western concepts and non-western realities; A critique of the Eurocentric theory of nationalism; Methodology for voluntaristic theory; Some correlates of the Third World concept; Towards a new definition of Third World nationalism; A sociological definition of nationalism; The stages of proto-nationalism: tribalism, ethnicity and patriotism; Political evolution and concomitant types of social consciousness; Patriotism and nationalism differentiated.
Includes bibliographical references (pages 240-247) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Developing countries -- Politics and government; Nationalism -- Developing countries; Political culture -- Developing countries; Nationalisme -- Pays en voie de développement.; Culture politique -- Pays en voie de développement.; Pays en voie de développement -- Politique et gouvernement; POLITICAL SCIENCE -- Political Process -- General; Nationalism; Political culture; Politics and government; Developing countries; Nationalisme; Culturele aspecten; Developing countries -- Politics